Life in our new possessions - Devins, John Bancroft 1856-1911. (Boston American Tract Society, 1905)
"The complete book in PDF format"--CD-ROM label.
Distributed by FELTA Multi-Media.
Keywords: Philippines; Philippines -- History -- 1898-.